The physical nature of weak shock reflection - Ashworth, Jason Trevor (My University, 2006)
Recent high-resolution numerical studies of weak shock reflections have shown that a complex flow structure exists behind the triple point which consists of multiple shocks, expansion fans and triple points. This region had not been detected earlier in experimental observations or numerical studies of weak shock reflections due to the small size of this region. New components were designed and built to modify an existing large-scale shock tube in order to obtain experimental observations to validate the numerical results. The shock tube produced a large, expanding cylindrical incident wave which was reflected off a 15° corner on the roof of the section to produce a weak shock Mach reflection with a large Mach stem in the test section. The shock tube was equipped with PCB high-speed pressure transducers and digital scope for data acquisition, and a schlieren optical system to visualise the region behind the triple point. The tests were conducted over a range of incident wave Mach numbers (M12 = 1.060-1.094) and produced Mach stems of between 694 mm and 850 mm in length. The schlieren photographs clearly show an expansion fan centered on the triple point in all the successful tests conducted. In some of the more resolved images, a shocklet can be seen terminating the expansion fan, and in others a second expansion fan and/or shocklet can be seen. A ‘von Neumann reflection’ was not visualised experimentally, and hence it has been proposed that the four-wave reflection found in these tests be named a ‘Guderley reflection’. The experimental validation of Hunter & Tesdall’s (2002) work resolves the ‘von Neumann Paradox’.
Student Number : 9900131F - MSc (Eng) dissertation - School of Mechanical Engineering - Faculty of Engineering
Keywords: weak; shock; reflection; von Neumann Paradox